The fifth child - Lessing, Doris May, 1919- (New York : Vintage International, 1989)
Harriet Lovatt's life is torn apart when she gives birth to Ben, an insatiably hungry, abnormally strong, brutal child, who she cannot bear to leave in an institution, but whose presence in her home terrorizes her husband and other four children.
Wilson's Fiction.
Wilson's Fiction, October 2010.
Adult
Keywords: Families -- England -- Fiction; Mothers and sons -- England -- Fiction; Family life -- Fiction; Mother-son relationship -- Fiction; England -- Fiction